Terrence H. Witkowski: the making of a marketing and consumption historian. (18th February 2019) - Witkowski, Terrence H.
Abstract : Purpose: This paper aims to present an autobiographical account on the life of Terrence H. Witkowski and his development as a marketing and consumption historian. Design/methodology/approach: This paper is an autobiography and intellectual history. Findings: The author traces his interest in history to childhood travel, to growing up in a home furnished with early American décor and to a lifelong passion for antique collecting. Historical research in marketing and consumption fit his independent personality, and has made the best use of his scholarly skill set. Originality/value: This essay describes one person's journey to becoming a marketing and consumption historian.